For all positive integers n , the sequence { a n } and S n satisfy:
S n = k = 1 ∑ n a k a n + S n = 2 n
Find the value of n → ∞ lim a n .
This problem is a part of <Inconsequences!> series .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Firstly, note that: ( a n + 1 + S n + 1 ) − ( a n + S n ) = 2 reads 2 a n − a n − 1 = 2 ( 1 ) Also, a 1 = 1 now from (1) we can calculate successive terms to obtain a 2 = 2 3 , a 3 = 4 7 e t c . To which I conjecture that the sequence is strictly monotonic increasing and bounded above by 2.
Claim 1: a n < 2 Proof: By induction (using (1)) a n + 1 = 1 + 2 a n < 1 + 2 2 = 2
Claim 2: a n + 1 > a n Proof: By induction again: a n + 1 − a n = 1 − 2 a n > 0
Hence, by the Monotonic Sequences Theorem, a n converges, to say a ∈ R . That is a n → a a s n → ∞ . Therefore, by (1): n → ∞ lim ( 2 a n − a n − 1 ) = 2 a − a = a = 2
(Note: I'm aware that I did skip a few details in the induction )
Let us assume { a n } is a convergent sequence . Hence we can use Cauchy's First Limit Theorem which states that the limit of the sequence { a n } is equal to the limit of the Arithmetic mean of the terms of the sequence provided the limit of the sequence exists.
Hence n → ∞ lim n S n = n → ∞ lim a n .
So using the second equation :-
n → ∞ lim ( n a n + n S n ) = 2 .
But since a n is assumed to be convergent it must be necessarily bounded. So n → ∞ lim n a n = 0 .
Hence n → ∞ lim n S n = 2 .
But using the above theorem....this limit is the same as the limit of the sequence .
Hence n → ∞ lim a n = 2 .
Note:- I have assumed the convergence of { a n } since it was asked in the question. Otherwise we can also proceed as @Chew-Seong Cheong did to establish the recurrence relation 2 a n + 1 = a n + 2 and then use this to prove the convergence of the sequence.
Problem Loading...
Note Loading...
Set Loading...
Let us first work out the recurrence relation of { a n } .
a n + S n a n + 1 + S n + 1 ( 2 ) − ( 1 ) : a n + 1 − a n + S n + 1 − S n a n + 1 − a n + a n + 1 ⟹ a n + 1 = 2 n = 2 ( n + 1 ) = 2 ( n + 1 ) − 2 n = 2 = 2 a n + 1 . . . ( 1 ) . . . ( 2 ) . . . ( 3 )
Form (1): a n + S n = 2 n ⟹ a 1 + S 1 = 2 ⟹ a 1 + a 1 = 2 ⟹ a 1 = 1 . Then using (3):
a 1 a 2 a 3 = 1 = 2 a 1 + 1 = 2 3 = 4 3 + 1 = 4 7 = 2 1 − 1 2 1 − 1 = 2 2 − 1 2 2 − 1 = 2 3 − 1 2 3 − 1
From the first few n , it appears that we can claim that a n = 2 n − 1 2 n − 1 . Let us prove by induction that the claim is true for all n ≥ 1 .
Proof:
For n = 1 , a 1 = 2 1 − 1 2 1 − 1 = 1 . Therefore, the claim is true for n = 1 .
Assuming the claim is true for n , then from (3):
a n + 1 = 2 a n + 1 = 2 n − 1 ⋅ 2 2 n − 1 + 1 = 2 n 2 n − 1 + 2 n = 2 n + 1 − 1 2 n + 1 − 1
Therefore, the claim is also true for n + 1 and hence true for all n ≥ 1 . □
Now, we have:
n → ∞ lim a n = n → ∞ lim 2 n − 1 2 n − 1 = n → ∞ lim ( 2 − 2 n − 1 1 ) = 2